Design Of Sales Application With Data Mining Using Analysis Basket Market Methodand Apriori Algorithm In The Jetlag Coffee: Design Of Sales Application With Data Mining Using Analysis Basket Market Methodand Apriori Algorithm In The Jetlag Coffee - Wargijono Utomo; Aga Dwijayanti Purnomo (Jurnal Mantik, 2020)
The tight competition in sales, made the owner of Jetlag Coffe must be smart in analyzing the market. In addition, the availability of goods sold is one of the factors that must be analyzed so that customer needs can be met. To support this, previous sales data can be used to analyze the market and customer needs with market basket analysis. Addition of a priori algorithms including the types of association rules in data mining, a priori algorithms that aim to find items sets run on a set of data. Based on this relationship, it is possible to promote goods with a pattern of attachment to the item. Consumers who purchase products will be interested in purchasing different products, than those usually purchased by other consumers before. By offering products contained in the pattern of sales of these products. By using this market basket analysis and a priori algorithm method, it is hoped that it can also optimize the database, increase sales, and minimize product promotions that have low sales levels. By minimizing the promotion of goods that are not bought, consumers will not be disturbed by the promotion of products that do not have a pattern of attachments, so that promotions will be more effective.